The Passenger Terminal at Suvarnabhumi International Airport and Thai Identity in the Midst of Globalization Era - Koompong Noobanjong (My University, 2018)
Aside from functioning as a strategic instrument for modernization process and economic development,international airports represent a material embodiment for cultural identity of their host nations as evident fromthe architecture of passenger terminals around the world. Via semiological and phenomenological theories,this article presents a critical inquiry on the passenger terminal at Suvarnabhumi International Airport in Thailandin both cultural and social dimensions. The research also investigates the complex dynamism of the Thaiidentity discourse (known as Thainess or khwampenthai) during the age of globalization, which has resulted incontradictory readings on the building’s ultra-modern appearance in terms of a dichotomy between place-nessand placeless-ness. Not only do the aforementioned studies reveal paradoxical characteristics of the Thaiidentity through the complexity, incongruity, and contradiction in architectural signification by the passengerterminal at Suvarnabhumi, but critical examinations on the design of this aviation facility further expose somefundamental problems in the discourse of Thainess as well.
Keywords: Dynamism; Aside; Contradiction; International airport; Socioeconomic Development in Asia